Improving the Traction Properties of the Shunting Diesel Locomotives ChME3 by Distributing the Traction Force Between the Axles of the Diesel Locomotive - Riabov, Ye. S.; Yeritsyan, B. Kh.; Lysenko, Ye. V.; Chernyshenko, Ye. G.; Zhukov, A. Yu. (Science and Transport Progress, 2025)
Purpose. Research into the specific determination of the influence of redistribution of traction force between axles on increasing the traction properties of the ChME3 diesel locomotive. Methodology. A mathematical model has been developed to determine the coefficient of utilization of the coupling mass of the ChME3 diesel locomotive when redistributing the tractive effort between the axles of the diesel locomotive. It is shown that as a result of the action of forces in the gear meshing of traction reducers and the action of the traction force on the automatic coupling, the unloading of the first, second, and fourth axles and the loading of the third, fifth, and sixth axles occurs in the direction of movement of the locomotive. Finding. Calculations of the coefficient of utilization of the traction mass of a diesel locomotive were carried out at different values of the coefficient of coupling and different schemes of power supply of traction electric motors. It was determined that the highest values of the coefficient of utilization of the traction mass of a locomotive are achieved in the case of individual power supply and control of traction electric motors. This method of power supply allows for the most accurate consideration of the actual axle load when redistributing the tractive effort between the axles of the locomotive. With group power supply of traction motors, in the case of combining axles with close axle coupling mass utilization coefficients, almost full utilization of coupling mass is also achieved. At the same time, the value of the coefficient of utilization of the traction mass of the diesel locomotive is stable and practically does not depend on the traction force. With by-bogie power supply and group power supply of all electric motors, the coupling mass utilization coefficient varies in the range of 0.8…0.87, with lower values being achieved at higher traction force of the diesel locomotive. Originality. The possibility of increasing the traction properties of the ChME3 diesel locomotive by redistributing traction forces between the axles of the diesel locomotive, taking into account the redistribution of the actual axle load, is substantiated. Rational options for power supply schemes for traction electric motors have been identified, which ensure a high utilization factor of the traction mass of the diesel locomotive. Practical value. The results obtained can be used in the modernization of ChME3 diesel locomotives, which allows to increase their traction properties. The proposed approach to improving traction properties can be applied to other traction rolling stock.